2005
DOI: 10.1111/j.1467-9442.2005.00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Mobility under Private vs. Public Education*

Abstract: Intergenerational earnings mobility is analyzed in a model where human capital is produced using schooling and parental time. In steady states more mobile societies have less inequality, but in the short run higher mobility may result from an increase in inequality. Starting from the same inequality, mobility is higher under public than under private education. A rise in income shocks, for example due to increased returns to ability, or a switch from public to private schooling both increase inequality. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 29 publications
(42 reference statements)
1
32
0
1
Order By: Relevance
“…Solon (1999) theoretical model reveals that a more progressive public investment in human capital tends to increase mobility. Another theoretical model by Davies, Zhang and Zeng (2004) affirms that "starting from the same inequality, mobility is higher under public than under private education". However, an empirical study of Britain by Blanden, Gregg and Machin (2005) found that "the big expansion in university participation has http://dx.doi.org/10.15405/epsbs.2016.08.123 eISSN: 2357-1330 in two ways, combining extensive descriptive analysis of progress in educational attainment with a more formal evaluation of intergenerational social mobility using indices constructed by Dahan and Gaviria (2001) and Behrman, Birdsall and Szekely (1998).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Solon (1999) theoretical model reveals that a more progressive public investment in human capital tends to increase mobility. Another theoretical model by Davies, Zhang and Zeng (2004) affirms that "starting from the same inequality, mobility is higher under public than under private education". However, an empirical study of Britain by Blanden, Gregg and Machin (2005) found that "the big expansion in university participation has http://dx.doi.org/10.15405/epsbs.2016.08.123 eISSN: 2357-1330 in two ways, combining extensive descriptive analysis of progress in educational attainment with a more formal evaluation of intergenerational social mobility using indices constructed by Dahan and Gaviria (2001) and Behrman, Birdsall and Szekely (1998).…”
Section: Literature Reviewmentioning
confidence: 99%
“…27 Notice that the regional ranking by social mobility broadly coincides with the rankings according to inequality. Although, of course, the two concepts are different and can move in the opposite directions, it has been suggested that they are unlikely to do so (Davies et al 2005). …”
mentioning
confidence: 99%
“…However, differently from them, we include random ability, while neglecting kids' effort in the process of formation of human capital. Similar, more recent, contributions include Bénabou (1996), Fernández and Rogerson (1998), Davies, Zhang and Zeng (2005. 7 the parent (see Bowles and Gintis 2002, Sacerdote 2002, Plug and Vijverberg 2003, and references therein), which implies that p lies in some range of (0.5, 1).…”
Section: Imperfect Information and Social Mismatchmentioning
confidence: 99%